Replacing Dry Barley Beans with Sprouting Barley by (20-40) % in the Productive Efficiency of Awassi Lambs (Journal of Hama University, 2024)
The research was conducted in one of the private lambs fattening farms in the Damascus countryside governorate on 15 lambs whose weight ranged between (24-25) kg. (Group I: The control group. Group II: replaced the dry barley with barley culture with 20% of the concentrated ration. Group III: The dry barley was replaced with the barley culture with 40% of the concentrated ration.) The experiment lasted for 60 days, preceded by a 10-day preparatory feeding period, and the feed mixtures were close in nutritional value in terms of energy and protein according to the nutritional needs of the age group according to the American Food Standard (NRC, 1985) and differed among themselves by the percentage of cultivar barley, and the indicators were studied The following productivity (live weight - weight gain - the amount of feed consumed - food conversion factor - economic feasibility).The results showed a significant increase at the level (P
Keywords: Cultivated Barley; Productivity Indicators; Economic Feasibility; Awassi Lambs